(untitled) (Global Journal of Management and Business Research, 2023)
Abstract- The study seeks to show the life cycle ranking of actors roles and access to actors and other environmental factors effect on various biopharmaceutical entrepreneurial ecosystems in Central Europe from the perspective of the various actors within the ecosystems The study finds several interesting results First the majority of actors view their ecosystem to be in the growth stage of the life cycle Second the majority of actors perceive their ecosystem as developing via existing actors Third there is some variation among the ecosystems in terms of which actors played the most important roles in developing the ecosystem with those in academia playing the highest role Yet all actors are perceived as playing a role in the development of the ecosystem by most suggesting the additive nature of ecosystem development